Occurrence of Knipowitschia goerneri Ahnelt, 1991 (Gobiidae) in southern Albania confirmed with molecular tools. (2nd February 2017) - Vukić, J.; Ulqini, D.; Šanda, R.
Summary: The aim of this work was to identify the newly discovered population of Knipowitschia from southern Albania using molecular methods. Samples were collected from the Butrint Lagoon catchment with seine nets. Mitochondrial cytochrome b and nuclear ribosomal protein gene (S7) were analyzed. A nuclear marker was used for the first time to study relationships between and among Knipowitschia species. The results show that the population from Albania belongs to Knipowitschia goerneri Ahnelt, 1991 (Corfu dwarf goby), a species previously thought to be endemic to the Korission Lagoon catchment on Kerkyra Island, Greece. Based on both mitochondrial and nuclear markers, this species was recovered in a well‐supported Ionian clade also comprising Knipowitschia milleri (Ahnelt & Bianco, 1990) (Acheron spring goby) from the Acheron River and the Knipowitschia population from Trichonis Lake.